Integration the 6th category Business Excellence Framework, the 8th clause ISO 9001:2015 and the 6th category KPKU Indonesia Framework - widaningrum, sri; Mohammad, Musli; Ibrahim, M. Rasidi (International Journal of Integrated Engineering, 2020)
Abstract: KPKU (Kriteria Penilaian Kinerja Unggul) Indonesia framework 2015 adopted Business Excellence Framework 2013-2014, that is a framework used by the â€œMinistry of State-Owned Enterprisesâ€ of the Republic of Indonesia to assess the performance of SOEs in Indonesia. One of the KPKU criteria is the operation, that is the most dominant criteria in company performance. They are proven by the score in Baldrige Excellence Framework (110 point is the highest score) for product and process results which are influenced by operational criteria in the 6th category of BEF. Currently, Indonesia does not have yet business excellence framework based on companies in Indonesia and does not have yet Indonesia operational excellence model, either in Indonesia or based on previous research. Currently, there is no model that integrates (Baldrige Excellence Framework, ISO 9001: 2015, and KPKU). This research will develop the Indonesia operational excellence model based on the Baldrige Excellence Framework, ISO 9001:2015, and KPKU Indonesia framework. Stage of the research is the literature survey, identifying the 6th Category Baldrige Excellence Framework; KPKU and the 8th Clause ISO 9001:2015, and integration the 6th KPKU framework and the 8th Clause ISO 9001:2015 to the 6th Category Baldrige Excellence framework. The results of the study are the Indonesian operational excellence framework that consists of 5 criteria and 14 sub-criteria, namely Product and Process Design, Process Management, Process Efficiency and Effectiveness, Process Improvement, and Safety and Emergency Preparedness. This model is appropriate for company performance measurement, especially operational performance. Keywords: Integration, Baldrige Excellence Framework, ISO 9001:2015, KPKU, operational excellence.